Four Reasons Why There Is No “Poverty Trap” In Rural China - Zhizhang , Wang; Xia , Tan; Zhihong, Yang (Razón Crítica, 2022)
In 2020 China eliminated the overall regional poverty and finished the arduous task of solving the problem of absolute poverty. Even though there is an actual lingering problem of relative poverty, the objective risk of falling into a poverty trap in China’s underdeveloped regions does not reasonably exist. This article analyzes four perspectives to underpin such statement: the institutional, the historical, the individual, and the spiritual power.